2016
DOI: 10.1177/1557988315595858
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Disease and Depression Among Hispanic Americans

Abstract: Hispanic Americans are the fastest growing minority group in the United States. They face a distinct set of health challenges, resulting in persistent health disparities. Chronic disease self-management programs hold promise in addressing individual-level, behavioral risks factors, such as dietary habits and physical activity patterns. In light of the unique barriers Hispanic men face, including low participation in evidence-based health intervention research, this article argues for a gendered perspective whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…The results showed that individuals who reported many chronic diseases reported more depressive symptoms 8 years later. This finding is in line with studies that have illustrated positive associations between chronic diseases and depressive symptoms (Black, Markides, & Ray, 2003; Chan & Corvin, 2016). It supports findings that underline the comorbidity of depressive symptoms with chronic physical diseases such as arthritis, heart problems, and diabetes in Hispanic Americans.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results showed that individuals who reported many chronic diseases reported more depressive symptoms 8 years later. This finding is in line with studies that have illustrated positive associations between chronic diseases and depressive symptoms (Black, Markides, & Ray, 2003; Chan & Corvin, 2016). It supports findings that underline the comorbidity of depressive symptoms with chronic physical diseases such as arthritis, heart problems, and diabetes in Hispanic Americans.…”
Section: Discussionsupporting
confidence: 92%
“…It supports findings that underline the comorbidity of depressive symptoms with chronic physical diseases such as arthritis, heart problems, and diabetes in Hispanic Americans. On one hand, studies have shown that individuals with one or more chronic diseases have an increased risk of experiencing major depressive symptoms (Chan & Corvin, 2016). On the other hand, somatization literature shows that individuals with depression can also experience physical illnesses (Black et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the Latino culture values “marianismo” as a virtue in which women must emulate the Virgin Mary in selflessness, caring, and sacrifice for their family (Sanchez et al, 2018). Latino women may thus avoid seeking mental health care for fear of affecting their children’s well-being or even losing their families (Chan & Corvin, 2016). Furthermore, the Latino culture observes a characteristic of an external locus of control characteristic by which individuals believe that outside forces, such as fate, luck, and divine influences control their life circumstances and outcomes (Timmins & Martin, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, as this instrument was developed and tested with a population of men who had been diagnosed with prostate cancer, it is important to broaden the scope of the measure to access conceptions of masculinity that are not tied to a single diagnostic group. For example, Chan and Corvin (2016) conducted a qualitative investigation finding links between masculinity, depression, and chronic diseases such as cardiovascular disease, diabetes, and hypertension, finding a complex interplay of contextual factors. Of particular interest in a broader chronic disease population is the role of sexual identity in masculinity.…”
mentioning
confidence: 99%